Single-Cell RNA Sequencing on Formalin-Fixed and Paraffin-Embedded (FFPE) Tissue Identified Multi-Ciliary Cells in Breast Cancer - Silvia González-Martínez; José Palacios; Irene Carretero-Barrio; Val F. Lanza; Mónica García-Cosío Piqueras; Tamara Caniego-Casas; David Hardisson; Isabel Esteban-Rodríguez; Javier Cortés; Belén Pérez-Mies (Cells)
The purpose of this study was to evaluate the suitability of formalin-fixed and paraffin-embedded (FFPE) samples and fixed fresh (FF) samples for single-cell RNA sequencing (scRNAseq). To this end, we compared single-cell profiles from FFPE and matched FF tissue samples of one invasive carcinoma of no special type carcinoma (invasive ductal carcinoma–IDC) and one invasive lobular carcinoma (ILC) to assess consistency in cell type distribution and molecular profiles. The results were validated using immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), and electron microscopy. Additionally, immune cell proportions identified by IHC were quantified using QuPath and compared to the scRNAseq results. FFPE- and FF-derived libraries demonstrated high-quality sequencing metrics, and cellular heterogeneity was similar. No exclusive cell populations were identified by either approach. The four samples analysis identified six types of epithelial cells, as well as tumoral microenvironment populations. The scRNAseq results from epithelial neoplastic cells were concordant with common IHC markers. The proportion of immune cells identified by IHC in FFPE sections were similar to those obtained by scRNAseq. We identified and validated a previously poorly recognized subpopulation of neoplastic multi-ciliated cells (MCCs) (FOXJ1, ROPN1L). Analysis of FOXJ1 in 214 ER-positive invasive carcinomas demonstrated protein expression in one third of tumors, suggesting frequent focal MCC differentiation. Our results support the suitability of scRNAseq analysis using FFPE tissue, and identified a subpopulation of neoplastic MCC in breast cancer.